A review of clinical treatment considerations of donepezil in severe Alzheimer's disease. (29th July 2018) - Adlimoghaddam, Aida; Neuendorff, Melanie; Roy, Banibrata; Albensi, Benedict C.
Summary: Background: Alzheimer's disease (AD) is a neurodegenerative disorder that affects over 45 million people worldwide. Patients with severe AD require help with daily activities and show severe memory impairment. Currently, donepezil is one of two drugs approved by FDA and Health Canada for the treatment of severe AD (MMSE score <10). It is prescribed as 5 or 10 mg/d and an FDA‐approved 23‐mg/d dose. Method: This review will discuss risks and benefits of donepezil at these doses in severe AD. Articles were identified using PubMed using the MeSH terms "donepezil" AND "Alzheimer Disease" AND "severe." Three double‐blind, placebo‐controlled, randomized studies, one post hoc analysis, and one subgroup analysis were selected. Results: Donepezil was found to benefit patients in cognition and global functioning. The most consistent improvement was in severe impairment battery (SIB) scores. However, more patients treated with high dosage of donepezil discontinued their treatment due to various adverse events (AEs). Conclusion: Clinicians must weigh benefits against adverse events when determining the course of therapy, as recommendations for cholinesterase inhibitors in advanced AD remain unclear and vary with different guidelines.